2015
DOI: 10.1364/ol.40.003089
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of super-thermal photon-number statistics in second-harmonic generation

Abstract: Changes in the statistical properties of light undergoing second-harmonic generation are investigated in the photon-number-resolving domain. We theoretically demonstrate that when a portion of multimode thermal light produced by parametric down-conversion is up-converted, both the second-harmonics and the residual beam at the fundamental wavelength are endowed with super-thermal photon-number distributions. The experimental results, which were obtained by exploiting the photo-number-resolving capability of hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In Section 2.1, we briefly report the well-known classical description of SHG focusing on the transformation of the statistics in the cases of coherent and chaotic light. In particular, we resume the results of a previous work by us, where, by applying a semiclassical approach, we have demonstrated [11] that the second-harmonic of a fundamental beam featuring multi-mode thermal statistics exhibits a more-than-thermal, namely superthermal, statistics. In Section 2.2, we approach the quantum model.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In Section 2.1, we briefly report the well-known classical description of SHG focusing on the transformation of the statistics in the cases of coherent and chaotic light. In particular, we resume the results of a previous work by us, where, by applying a semiclassical approach, we have demonstrated [11] that the second-harmonic of a fundamental beam featuring multi-mode thermal statistics exhibits a more-than-thermal, namely superthermal, statistics. In Section 2.2, we approach the quantum model.…”
Section: Introductionmentioning
confidence: 60%
“…where L is the crystal length. Given the link between the incoming light intensity and the second-harmonic one in Equation 10, it is possible to find a relation between the two corresponding light distributions [11,14,15]. Upon writing Equation 10as…”
Section: Classical Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that when the second-harmonic generation process is applied to the multi-mode thermal eld described by Eq. (1) the second-harmonic eld is characterised by a di erent statistics [14]. In particular, by using a classical approach it is possible to demonstrate that the photon-number distribution for detected photons is given by…”
Section: Super-thermal Statisticsmentioning
confidence: 99%
“…However, there are situations in which the values of F and g ( ) are not sensitive enough to distinguish between similar states. An example is given by the super-thermal states with a large number of modes [14]. In this case, a possible alternative measurement is given by the calculation of the photon-number correlations between the two outputs of a beam splitter at which the light under study has been divided.…”
Section: Super-thermal Statisticsmentioning
confidence: 99%